Час пик для новобрачных: [повесть] / Татьяна Полякова - Полякова Татьяна Викторовна (Детектив глазами женщины, 2002)
Экземпляры: К.Х. (20200316) / Инвентарный номер: 47743 / Цена: 56.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: П 54 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44